Age Is the Only Predictor of Poor Bowel Preparation in the Hospitalized Patient - Julia McNabb-Baltar; Alastair Dorreen; Hisham Al Dhahab; Michael Fein; Xin Xiong; Mike O’ Byrne; Imene Ait; Myriam Martel; Alan N. Barkun (Canadian Journal of Gastroenterology and Hepatology)
We examine the impact of key variables on the likelihood of inpatient poor bowel preparation for colonoscopy. Records of inpatients that underwent colonoscopy at our institution between January 2010 and December 2011 were retrospectively extracted. Univariable and multivariable logistic regression models were fitted to assess the effect of clinical variables on the odds of poor preparation. Tested predictors included age; gender; use of narcotics; heavy medication burden; comorbidities; history of previous abdominal surgery; neurological disorder; product used for bowel preparation, whether or not the bowel regimen was given as split or standard dose; and time of endoscopy. Overall, 244 patients were assessed including 83 (34.0%, 95% CI: 28.1–39.9%) with poor bowel preparation. Cecal intubation was achieved in 81.1% of patients (95% CI: 76.2–86.0%). When stratified by quality of bowel preparation, cecal intubation was achieved in only 65.9% (95% CI: 60.0–71.9%) of patients with poor bowel preparation and 89.9% (95% CI: 86.1–93.7%) of patient with good bowel preparation. In multivariate logistic regression analysis, only advancing age was an independent predictor of poor bowel preparation (OR = 1.026, CI: 1.006 to 1.045, and p=0.008). Age is the only independent predictor of poor bowel preparation amongst hospitalized patients.